Climate-Smart Food - Reay, Dave (Springer Nature, 2019)
This open access book asks just how climate-smart our food really is. It follows an average day's worth of food and drink to see where it comes from, how far it travels, and the carbon price we all pay for it. From our breakfast tea and toast, through breaktime chocolate bar, to take-away supper, Dave Reay explores the weather extremes the world's farmers are already dealing with, and what new threats climate change will bring. Readers will encounter heat waves and hurricanes, wildfires and deadly toxins, as well as some truly climate-smart solutions. In every case there are responses that could cut emissions while boosting resilience and livelihoods. Ultimately we are all in this together, our decisions on what food we buy and how we consume it send life-changing ripples right through the global web that is our food supply. As we face a future of 10 billion mouths to feed in a rapidly changing climate, it's time to get to know our farmers and herders, our vintners and fisherfolk, a whole lot better. ;